STRATEGI MOCHTAR LUBIS DALAM MEMPERTAHANKAN PROPAGANDA ORDE BARU MELALUI BUKU CERITA PENDEK KULI KONTRAK - Putra, Heru Joni (Puitika, 2016)
This paper shows Mochtar Lubisâ€™ Kuli Kontrak has the political relations with the New Orderâ€™s negative stigma of communism; Kuli Kontrak was culturally part of spreading the stigma. Every element in the short stories collection has different functions, but interrelated, in maintaining the negative stigma. The elements discussed in this paper, first, the intrinsic elements, namely the narrative strategy is divided into three main parts. Second, extrinsic elements: namely the covers which contains a painting and endorsements from figures. Third, the political element: the year of publication of the book and political backgrounds in Indonesia at that time. Discussion of each element followed by politics of aesthetics analysis, namely analysis of the political impacts of the use of these elements to social conditions, either directly or indirectly, expected by the author or not.Â